The Development of Engklek Game Media Based on Higher Order Thinking Skills in Learning Science of Class V Elementary School - Zahrah Kholidah; Prima Mutia Sari (Jurnal Penelitian Pendidikan IPA, 2023)
The students still have a limited understanding of science learning, particularly the topic of food chains, due to the lack of diverse media, resulting in less engaging lessons that fail to spark the students' enthusiasm to actively participate in the learning process. This research aims to determine the feasibility of an engklek game medium based on higher-order reasoning skills in science learning in the V grade elementary school. This research uses the ADDIE model development research, which includes five phases: analysis, development design, implementation and evaluation. Data collection using questionnaires and observations. The research sample consisted of teachers and 5th grade students of one of the public elementary schools in Bogor regency. Media validation through media expert tests achieved a score of 84% with a very good category, material validation achieved a score of 83% with a very good category. After conducting tests, students and teachers also give ratings on the game media created. Based on the results obtained, it shows that the engklek game media based on higher-order thinking skills are suitable for instilling higher-order thinking skills in the participants.